2009
DOI: 10.1107/s0021889809043957
|View full text |Cite
|
Sign up to set email alerts
|

Micropipe-induced birefringence in 6H silicon carbide

Abstract: International audienceThe micropipe-induced birefringence of 6H silicon carbide (SiC) is measured and quantitatively modelled. A good agreement can be obtained between theory and experiment, provided that background residual stress is added to the local dislocation-induced stress. Observations are compatible with or predictable from the Burgers vector values, and birefringence is shown to be an interesting tool for probing the nature of the dislocations associated with e. g. micropipes; it is also faster than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…In a former publication [11], we showed that a close agreement could be obtained between experimental and simulated birefringence patterns induced by micropipes. However, since those micropipes are associated with large Burgers vector length, they cannot give the limit of detection of the method.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…In a former publication [11], we showed that a close agreement could be obtained between experimental and simulated birefringence patterns induced by micropipes. However, since those micropipes are associated with large Burgers vector length, they cannot give the limit of detection of the method.…”
Section: Introductionsupporting
confidence: 64%
“…We use Zeiss Neofluar objectives with a magnification ranging from  2.5 to  100, and polarized green light with wavelength l¼540 nm. The measurement principles and modeling have already been thoroughly discussed in [11], so that they will not be repeated here. The reader can consult this reference for calculation details.…”
Section: Birefringence Experimentsmentioning
confidence: 99%
See 3 more Smart Citations